UNLOCKING LEARNING: THE POTENTIAL OF EDUCATIONAL ESCAPE GAMES FOR MEANINGFUL MATHEMATICS EDUCATION (Interdisciplinary Studies Journal, 2025)
Mathematics education faces significant challenges, particularly in fostering meaningful learning that enables students to integrate new knowledge into their existing cognitive structures. Traditional methods often emphasize rote memorization rather than conceptual understanding, leading to disengagement and superficial learning. In response, educational Escape Games have emerged as an innovative approach to enhancing student motivation, engagement, and problem-solving skills. This study explores the potential of Escape Games as pedagogical tools by establishing key design criteria that ensure their effectiveness in educational settings. These criteria include balancing cognitive challenge and accessibility, integrating meaningful learning principles, and fostering collaboration through immersive narratives and well-structured puzzles. Methodologically, this study was conducted as qualitative research, based on a literature review and the analysis of previous studies on educational escape games, combined with an autoethnographic approach through the systematic testing of escape games. Additionally, this research examines how digital tools can support the development of Escape Games that align with curricular objectives while maintaining an engaging and interactive experience. By analyzing existing educational Escape Games and identifying best practices, this study provides a framework for designing games that promote deeper conceptual understanding and active participation. The findings suggest that when carefully structured, Escape Games can serve as powerful tools for transforming traditional learning environments into dynamic and stimulating spaces that encourage critical thinking and knowledge retention.
Keywords: educational escape games; Meaningful Learning; Mathematics education